2023
DOI: 10.3390/biom13040601
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 Family in Cancer: Signaling Mechanisms and Therapeutic Advances

Abstract: The 70 kDa heat shock proteins (HSP70s) are a group of highly conserved and inducible heat shock proteins. One of the main functions of HSP70s is to act as molecular chaperones that are involved in a large variety of cellular protein folding and remodeling processes. HSP70s are found to be over-expressed and may serve as prognostic markers in many types of cancers. HSP70s are also involved in most of the molecular processes of cancer hallmarks as well as the growth and survival of cancer cells. In fact, many e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 209 publications
0
4
0
Order By: Relevance
“…Interest in the development of drugs targeting protein quality control machinery has grown over the last two decades. , The possibility of Hsp70s as drug targets has not escaped the notice of researchers, ,,, including our group. It has been shown that Hsp70s are often overexpressed in cancers and that this correlates with a poor prognosis, however, given cancer types overexpress specific Hsp70s. , Why a specific Hsp70 would be upregulated in each cancer and how this related to other transforming events remain a mystery. Based on data presented here, it seems possible that a given Hsp70 might become misregulated and this Hsp70 would have distinct client proteins, which would predict that a given Hsp70 would correlate with a given set of oncogenic drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the development of drugs targeting protein quality control machinery has grown over the last two decades. , The possibility of Hsp70s as drug targets has not escaped the notice of researchers, ,,, including our group. It has been shown that Hsp70s are often overexpressed in cancers and that this correlates with a poor prognosis, however, given cancer types overexpress specific Hsp70s. , Why a specific Hsp70 would be upregulated in each cancer and how this related to other transforming events remain a mystery. Based on data presented here, it seems possible that a given Hsp70 might become misregulated and this Hsp70 would have distinct client proteins, which would predict that a given Hsp70 would correlate with a given set of oncogenic drivers.…”
Section: Discussionmentioning
confidence: 99%
“…We have also found that the presence of DnaK is associated with an increase in Reactive Oxygen Species and pro-inflammatory cytokine production, which may contribute to cancer onset and progression [ 66 ]. Highlighting the functional parallels between DnaK and the HSP70 protein family, it's important to note that the HSP70 family is overexpressed in various cancers, where they facilitate growth and survival of cancer cells [ 67 , 68 ]. This connection not only emphasizes DnaK’s critical contributions to cancer biology but also reinforces its importance as a focal point in cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…HSPA1A can support the survival and proliferation of cancer cells by stabilizing oncogenic proteins or promoting the degradation of tumor suppressors 20 . Additionally, HSPA1A has been implicated in the evasion of immune surveillance, allowing cancer cells to escape immune recognition and destruction 21 . Therefore, it is possible that the decreased expression of HSPA1A represents a protective mechanism initiated by the body to cope with the continuous genetic and cellular changes associated with tumor formation.…”
Section: Discussionmentioning
confidence: 99%